The Development of Articulate Storyline-based Learning Media to Improve 5th Grade Students’ Mathematical Representation Ability - Fery Muhamad Firdaus; Ika Nur Azizah; Sonia Pritin; Oktiana Damayanti; Fatika Chandra Annisa (IAIN Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to produce Articulate Storyline-based learning media on cubes and blocks nets material for fifth-grade elementary school students. This is Research and Development study. This study uses the ADDIE development procedure (Analysis, Design, Development, Implementation, Evaluation). The sample of this study was 26 fifth-grade students in an elementary school in Gunung Kidul, Yogyakarta. Expert judgment or validation is carried out by 2 media experts and 2 material experts to assess and revise the product. The method of data collection is a representation test, observation and questionnaires. The data analysis technique used content analysis and narrative analysis techniques. The result is a product of Articulate Storyline-based learning media on cubes and blocks nets material for fifth-grade elementary school students. The overall result of the trial shows good results, namely obtaining a decent category with details: (1) the material expert test got 3.8 or 76% good results, (2) the media expert test got 4.8 or 80% good results, (3) the results of the calculation of the n-gain score of 0.3877 which indicates an increase in students' mathematical representation abilities using articulate storyline-based learning media with moderate categories. So, it can be concluded that the Articulate Storyline-based learning media is good to be used as learning media on cubes and blocks in improving the mathematical representation abilities of fifth-grade elementary school students.Keywords: learning media, articulate storyline, mathematical representation, elementary school students. AbstrakPenelitian ini bertujuan untuk menghasilkan media pembelajaran berbasis articulate storyline materi jaring-jaring kubus dan balok pada siswa kelas V sekolah dasar. Penelitian ini merupakan penelitian pengembangan. Tahapan penelitian ini menggunakan prosedur pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Sampel penelitian ini adalah 26 siswa kelas V di salah satu sekolah dasar di Gunung Kidul, Yogyakarta. Uji ahli atau validasi dilakukan oleh 2 orang ahli media dan 2 orang ahli materi untuk menilai produk awal serta merevisi produk awal sesuai saran ahli. Metode pengumpulan data penelitian ini dengan tes representasi, observasi, dan angket. Teknik analsis data menggunakan teknik analisis konten dan analisis naratif. Hasil penelitian ini berupa produk media pembelajaran berbasis articulate storyline pada materi jaring-jaring kubus dan balok kelas V sekolah dasar. Keseluruhan hasil uji coba menunjukkan hasil yang baik yaitu memperoleh kategori layak dengan rincian: (1) uji ahli materi mendapatkan hasil 3,8 atau 76 % layak, (2) uji ahli media mendapatkan hasil 4,8 atau 80 % layak, (3) hasil perhitungan skor n-gain sebesar 0,3877 yang menunjukkan terjadi peningkatan kemampuan representasi matematis siswa dengan menggunakan media pembelajaran berbasis articulate storyline dengan kategori sedang. Sehingga dapat disimpulkan bahwa media pembelajaran berbasis articulate storyline layak digunakan sebagai media pembelajaran materi jaring-jaring kubus dan balok dalam meningkatkan kemampuan representasi matematis siswa kelas V sekolah dasar..Kata kunci: media pembelajaran, articulate storyline, representasi matematis, siswa sekolah dasar.